Knowledge Level of OTC and OTC Limited Drugs Use for Self-medication in the Community of Tondo Village, Mantikulore District, Central Sulawesi, Indonesia (Sciences of Pharmacy, 2022)
Self-medication is treatment without a doctor's prescription, based on the 2022 BPS, the percentage of self-medication for the people of Central Sulawesi in 2021 is 85.85%. The purpose of the study was to determine the characteristics of the community who did self-medication, minor illnesses that were treated with self-medication, the profile of over-the-counter (OTC) and OTC limited medicines for self-medication and the level of knowledge of these medicines use for self-medication in the community of Tondo Village. This type of research was descriptive with a sample of 386 respondents who were taken using purposive sampling. Time of data collection during August – November 2021. Based on the results, the respondents characteristics were female (52.3%) aged 26-35 (24.4%), household work (31.1%), history of high school education (46.4%). Minor illnesses that were treated using self-medication were fever (15.54%), ulcer (7.46%), cough (15.54%), flu (18.91%), diarrhea (2.85%), headache (1 .30%), and allergy (0.78%). The profiles of OTC and OTC limited drugs are limited to paracetamol for fever (33.16%), antacids for ulcers (75.70%), Komix® for coughs (28.8%), Mixagrib® for flu (36.99%), Entrostop® for diarrhea (70,00%), Ibuprofen for headaches (100%), and CTM for allergies (100%). Number of pharmacy or drug store was 61.46%. The selection of drugs were based on experience and personal/family usage history (84.46%), and the reason for self-medication was to save treatment costs (47.15%). The level of knowledge on the use of OTC and OTC limited drugs was categorized as good (75.09%). Based on the findings, we can conclude that the level of knowledge on the use of OTC and OTC limited drugs for self-medication of Tondo people is categorized as good.